Cultural Collision and Magical Transformation: The Plays of Tomson Highway - Nothof, Anne (Studies in Canadian Literature, 1995)
In Tomson Highway’s The Rez Sisters and Dry Lips Oughta Move to Kapuskasing, the cultural and spiritual values of Native and non-Native Canadians collide. The negative and positive consequences of cultural collision on characters leads, in some cases, to magical transformations. Nanabush, a central trickster figure in Native culture, aids in these transformations. Another area of cultural collision, the white audiences’ reception of these plays, also transforms the response to Native culture.